Online Training on Simple Website Development for Micro, Small, and Medium Enterprises in Desa Kelambir 5 - Supiyandi Supiyandi; Mardiah Mardiah; Rismayanti Rismayanti; Arie Rafika Dewi; Siti Sundari (Raskha Media Group, 2026)
Limited digital literacy is one of the main challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in Kelambir 5 Village in developing their businesses and expanding market reach. Most MSME actors are not yet able to use websites effectively as digital promotional media. This community service activity aims to enhance MSMEs' digital skills through online training on simple website development as a technology-based marketing tool. The method employed was a practice-based online training approach comprising needs assessment, core training, mentoring, and evaluation. The participants were 25 MSME actors selected purposively. Evaluation was conducted using pre-test and post-test instruments, as well as product-based assessment of the websites created by participants. The results indicate a significant increase in participants' understanding from an average of 30% to 82%, representing a 52% improvement. Furthermore, 80% of participants successfully developed functional websites for business promotion. The activity also contributed to behavioral changes in adopting digital marketing strategies and showed early economic impact through broader market reach. Therefore, practice-based online training is proven effective in improving MSMEs' digital capacity in a measurable and sustainable manner.